Effect of Peer Attachment on Legal Emotion Among Junior Middle School Students: The Mediation Role of Self-Esteem - Xu, Shuhui; Fan, Lu; Su, Chunjing (Frontiers in Psychology, 2022)
Legal consciousness is the individual consciousness that reflects legal phenomena. Well-developed legal consciousness plays a crucial role in informing citizens of their legal rights and ability to exercise these rights, therefore forming certain connections between individuals and society and its development is a key part of an individual’s socialization process. This study sought to focus on the emotional aspect of legal consciousness (henceforth legal emotion), and aim to investigate the effects of peer attachment on legal emotion with self-esteem as a mediator in early adolescents. A large sample of Chinese junior middle school students (N=967) completed a battery of self-reported questionnaires regarding legal emotion, peer attachment, self-esteem, prosocial tendencies, and interpersonal trust. Using a mediation model, we tested the effects of peer attachment on both positive and negative legal emotions mediated by self-esteem, while controlling for gender and age. The findings supported the mediation effects of peer attachment through self-esteem on legal emotions. In an additional preliminary investigation, we further showed that negative legal emotion acted as a mediator in the relationship between interpersonal trust and prosocial tendencies, which suggested that legal emotion is actively interacting with other self-related behaviors. The results provided first and important insights into the role of legal emotion, the emotional aspect of legal socialization, in the social interactions and its potential psychological mechanism, and might have important implications for education and intervention strategies to facilitate the legal socialization of adolescents.